Incidental focus on form and learner uptake in Iranian EFL classrooms - Pouriran, Yassamin; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2013)
This study investigated the connection between teachers’ incidental focus on form, namely, corrective feedback and learners’ uptake and immediate repair of errors in communicative English as a Foreign Language classrooms for adults. The data was drawn from the transcripts of oral corrective feedback moves of six audio and video-recorded classrooms at an intermediate level totaling 9 hours. Corrective feedback moves were coded based on Lyster and Ranta (1997) and Panova and Lyster (2002) models. This study investigated the integration of incidental focus on form into six intact communicative EFL classes. A descriptive design which employed qualitative data collection procedure was adopted. The results revealed a significant difference in the ratio of uptake following certain corrective feedback types, which was in sharp contrast to the findings of Lyster and Ranta (1997) and Panova and Lyster (2002). Possible reasons are discussed from different aspects of learners’ age, their motivation, and instructional settings.